O setor exportador cearense: uma análise do impacto da taxa de câmbio e da renda mundial - Mindêllo, Marlene Guilherme (2014)
In a context where markets are more unified between countries, the stability of the economic situation of a nation becomes a crucial factor for the performance of international trade, where the economic policies adopted by governments directly influence the performance of exports, now retracting, now expanding its performance. The exchange rate and world income as determinants of export performance, solids have discussed over the years and deserve close attention on the part of economic agents, because its increase can mean greater income generation and employment. Thus, this study aims to characterize the profile of the export sector in Ceará and test the possible relationship of existence in the long term as well as the degree of influence of the variables exchange rate and world income on the export performance of the state Ceará for the period 2000-2012. The methodology of this study adopted the most comprehensive VAR model called vector and error correction (VEC). The results show that, in the long run, the exchange rate and world income are relevant to explain oscillations in export dependent variable. On the other hand, in the short term, the analysis showed some lag time for imbalances occurring in the short term will be corrected in the long run. Identical behavior was found in the use of impulse response functions and variance decomposition of the error.